Dealignment in Costa Rica - Sánchez, F; Sánchez, Fernando F. (2004)
﻿ The erosion of partisan identification (i.e. dealignment) and its impact on the declining support for traditional parties has been widely documented in Western countries. However, this phenomenon does not appear to be a Western peculiarity. Costa Rica, Latin America's most stable democracy, seems to be following a similar hitherto unstudied path. The present thesis analyses electoral change in this nation. The study assesses whether Costa Rica is undergoing a long-term electoral change; and if so, how the process could be classified and explained. Moreover, it also evaluates how well the theories developed to explicate electoral change in Western democracies illuminate the Costa Rican case. The thesis is divided into five parts. Part I poses the research's methodological and theoretical framework. Part II contextualises the problem via a historical account of political parties' development, and an assessment of the electoral system. After analysing the main evidence of change in citizens' electoral behaviour and political attitudes, Part III characterises the process. Then, Part IV concentrates on explaining it. Finally, the central findings are presented in Part V. The thesis concludes that: 1) Costa Rica is undergoing a long-term electoral change process. This process can be defined as secular dealignment. 2) In the case studied, the erosion of citizens' partisan identification (partisan dealignment) has resulted in a growing electoral flux and the decline of electoral support for the traditional parties (electoral dealignment). 3) Dealignment in Costa Rica is basically caused by the decline of the PLN's (the country's oldest, most important party) historical loyalties. 4) The PLN's partisan identification is eroding due to the combination and mutual influence of political factors and social transformations. While many of the sociological determinants of dealignment in Costa Rica find parallels in developed democracies, some political factors seem to be specific to this country and most probably to Latin American nations. In general terms, this thesis demonstrates the relevance of in-depth, context-sensitive case studies for comparative electoral research, shows that such studies can be undertaken in Latin America, and highlights the theoretical and empirical benefits of election studies outside advanced industrial democracies.